Horses Referred to a Teaching Hospital Exclusively for Acupuncture and Herbs: A Three-Year Retrospective Analysis - Justin Shmalberg; Huisheng Xie; Mushtaq A. Memon (Medical Association of Pharmacopuncture Institute, 2019)
Equine acupuncture and herbal medicine are increasingly popular and have been anecdotally used in the treatment of a number of conditions. There is, however, a lack of data on the most commonly treated conditions in horses. The medical records of 164 horses presented exclusively for acupuncture and herbal therapy over a three-year period from October 2012 to October 2015 were evaluated from a mixed animal integrative medicine service at a veterinary academic teaching hospital. Horses were presented primarily for musculoskeletal conditions (62.0%), gastrointestinal disorders (9.5%), and anhydrosis (6.1%). Nearly half of all treated horses were geldings, and the mean age of treatment was 10.7 ± 6.5 years. The most common breeds were Warmbloods (28.2%), Quarter horses (20.2%), Thoroughbreds (17.8%), and Arabians (8.0%). Treatments included acupuncture (90.2%), herbal supplements (79.8%), electroacupuncture (69.9%), B12 injections (pharmacoacupuncture, 29.4%), or administration of autologous blood at acupuncture points (hemoacupuncture, 8.0%). Thirty-eight (38) different herbal formulas were recommended during the study period. Horses that were not provided herbal recommendations were more likely to present with gastrointestinal complaints (odds ratio = 11.2). Sex, breed, and presenting complaint had no or minimal impact on the types of treatments performed during the visit. However, data regarding patient characteristics and presenting complaints provide novel information which can be used to design prospective clinical trials. Keywords: acupuncture, Chinese herbs, equine, retrospective, veterinary